Characteristics and Antioxidant Activity of Fucoidan from Sargassum hystrix: Effect of Extraction Method - Amir Husni; Nuzulia Izmi; Fatimah Zahra Ayunani; Aprilia Kartini; Naila Husnayain; Alim Isnansetyo (International Journal of Food Science)
Fucoidan is a bioactive compound of brown seaweed with antioxidant characteristics. This study examined the aftermath of the extraction method on the yield, fucose content, xylose content, sulfate content, total sugar, antioxidant activity, and functional groups of fucoidan from Sargassum hystrix. The brown seaweed was extracted using 4 methods, namely, A (0.1 N HCl, room temperature, 24 h), B (2% CaCl2, 85°C, 4 h), C (85% ethanol, room temperature, 12 h), and D (0.5% EDTA, 70°C, 3 h). The antioxidant activity testing was carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH), Ferric-Reducing Antioxidant Power (FRAP), and Hydroxyl Radical Scavenging Activity (HRSA). The yield for methods of A, B, C, and D was 2.46±0.30, 0.68±0.34, 1.18±0.15, and 0.62±0.25%, with fucose content of 39.97±4.82, 26.72±3.38, 41.08±9.49, and 40.62±8.59%, xylose content of 8.07±0.92, 5.63±0.40, 6.80±0.83, and 7.83±1.83%, and the sulfate content of 11.47±2.20, 15.31±2.47, 30.62±2.76, and 27.80±3.59%. The result indicated the occurrence of a sulfate ester group in the functional group analysis with numerous similarities with the commercial fucoidan. The highest antioxidant activity of fucoidan from S. hystrix was found in method C, which was influenced by sulfate levels. Therefore, the extraction method of fucoidan from S. hystrix affects the characteristics and antioxidant activity.